OECD Multilateral Instrument: The New Era in International Tax Law - BACIA, Bartosz; TOPOROWSKI, Patryk (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).03, 2018)
The Multilateral Instrument to Implement Tax Treaty Related Measures to Prevent Base Erosion and Profit Shifting (MLI) is one action by the OECD to address tax-base erosion and profit shifting (BEPS), i.e., double non-taxation or strategies consisting of artificially shifting profits to low-tax locations where there is no substantial economic activity and at the same time, very little corporate tax being paid. MLI aims to modify bilateral double-taxation agreements. It is an international agreement that modifies, in an umbrella manner, the relevant provisions of bilateral double-taxation agreements. Standard clauses contained in the MLI should replace, modify or supplement the relevant clauses in bilateral agreements. MLI marks a new opening in international tax law, offering for the first time the ability to harmonize the rules governing cross-border taxation.